The Role of Management Functions in Enhancing Community Empowerment for Stunting Prevention in Batu Bara District - Herlina Sianturi; Reni Aprinawaty Sirait; Raisha Octavariny; Karnirius Harefa (Fakultas Kesehatan Masyarakat Institut Kesehatan Medistra Lubuk Pakam, 2026)
A Stunting remains a major public health problem in Indonesia, including in Batu Bara District. The success of stunting reduction is not only determined by technical interventions but is also influenced by the effectiveness of management functions and the level of community empowerment. This study aims to analyze the effect of basic management functions on community empowerment in stunting prevention efforts in the working area of the Batu Bara District Health Office. This study employed an analytical quantitative design with a cross-sectional approach. The population consisted of 250 stunting program implementers and posyandu cadres, with a sample of 167 respondents selected using proportional random sampling. Data were collected through a structured questionnaire that had been tested for validity and reliability. Data analysis was conducted using univariate, bivariate (Chi-square test), and multivariate (logistic regression) analyses. The results showed that all aspects of management functions planning, organizing, actuating, and controlling, had a significant effect on community empowerment (p < 0.001). The most dominant variable was controlling (PR = 5.84), followed by actuating (PR = 5.70), planning (PR = 4.32), and organizing (PR = 3.23). In conclusion, management functions play an important role in enhancing community empowerment in stunting prevention. Therefore, strengthening management functions, particularly in controlling and actuating, is necessary to improve the effectiveness of stunting prevention programs.